Influência da Força de Centrifugação na Viabilidade Espermática e Capacidade Fecundante In Vitro de Espermatozoides Bovinos - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Centrifugation by Percoll® gradient is the most widely used method in the preparation of bull sperm for the purpose of in vitro fertilization, however at the moment, no scientific study determined the best centrifugation speed to remove seminal plasma and other constituents, i.e. the speed at which the loss of sperm cells is minimized and where the spermatozoa in the pellet still remain functional. The present study was designed to examine the efficiency of different centrifugation forces in sperm separation Percoll by methods evaluating sperm quality parameters and subsequent development and quality of bovine in vitro production (IVP) embryos. Additionally, we evaluated oxidative stress parameters to verify a possible relationship with the findings in the sperm evaluation. In Experiment 1, the semen samples from each bull were pooled and submitted to centrifugation in discontinuous gradients Percoll (30,60 and 90%) at different forces: F1 (9000 X g), F2 (6500 X g), F3 (4500 X g) and F4 (2200 X g). In Experiment 2, the semen samples from each bull were done separately and submitted to: F1 (9000 X g) and F4 (2200 X g). All sperm samples were evaluated to the concentration, motility, vigor, morphology, reactive oxygen species (ROS) and integrity of the plasma membrane, and in experiment 2 also were evaluated lipid peroxidation, antioxidants assays and embryo development. No difference was observed in the concentration of sperm submitted to different centrifugation forces. In Experiment 1, the total percentage of motile sperm was increased (p < 0.05) after centrifugation in F3 and F4 and the ROS production to F1 was superior (p < 0.05) compared to other forces. In Experiment 2, when the bull semen was processed individually, no significant difference was observed in the sperm quality parameters assessment, lipid peroxidation, antioxidants assays, cleavage rate and average time of the first cleavage between F1 and F4, sires or interaction between them after Percoll. However, the increased force centrifugation reduced the rate of penetration and normal fertilization (P < 0.05). This work demonstrated for the first time that 2200 X g centrifugation force enhanced the penetration and fertilization rates in relation to usual centrifugation force (9000 X g) using sperm separation by discontinuous Percoll gradients in bovine. These findings suggest that this centrifugation force could be used with successful in the bovine IVP embryo since it does not reduce sperm recuperation and increases the fecundation rate.
Influence Of Centrifugation Force On Sperm Viability And Fertilizing Capacity Of Bovine Spermatozoa
Keywords: Seleção de espermatozoides; Gradientes de densidade; Centrifugação; Bovinos; Fecundação in vitro; Spermatozoa selection; Density-gradient centrifugation; Bovine; IVF; CNPQ::CIENCIAS AGRARIAS